Space invaders! - Albee, Sarah; Zalme, Ron (New York : Simon Spotlight, 1998)
The Rugrats babies become convinced that Earth is about to be invaded by space aliens.
"Based on the TV series, Rugrats, created by Klasky/Cuspo Inc. and Paul Germain as seen on Nickelodeon"--T.p. verso.
Keywords: Babies -- Fiction; Extraterrestrial beings -- Fiction